Study on the Electronic Structures and Optical Properties in Four Directions of Si-NWs Modified by Oxygen Atoms - Xue-Ke Wu; Song Zhang; Yan-Lin Tang (Advances in Condensed Matter Physics)
In this work, the first-principles study based on density functional theory was applied to investigate the geometries, electronic structures, and optical properties in four directions of the Si-NWs surface, which are modified by oxygen atoms. The results show that the geometries, band structures, and optical properties of the Si-NWs are affected by the modification of oxygen atoms. The Si─Si bonds adjacent to the region modified by oxygen atoms elongate, the cell volumes decrease, while the energy gaps of Si-NWs narrow. Evident impurity bands appear on the energy bands of the modified Si-NWs, forming S═O double bonds. A blue shift of the perpendicular component spectra of the dielectric constant relative to parallel spectra can be observed for Si [100]-NW, Si [111]-NW, and Si [112]-NW. At the same time, the real and imaginary parts of the dielectric function spectra of all Si-NWs are red-shifted after the modification by oxygen atoms, and the spectra of Si [111]-NWs forming Si═O double bonds are the most significant red-shifted. These results can provide a theoretical reference for preparing nano-silicon optoelectronic materials and devices.